2016
DOI: 10.1024/0301-1526/a000497
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for superficial vein thrombosis in patients with primary chronic venous disease

Abstract: Summary:Background: Primary chronic venous disease (CVD) is associated with an increased risk of superfi cial vein thrombosis (SVT). While CVD is a predominant factor in SVT, there is a range of additional predisposing factors. The objective was to investigate the association between age, gender, BMI, smoking, oestrogen hormone therapy, family history of venous thromboembolism (VTE) and CEAP clinical classifi cation in patients with CVD and a history of SVT. Patients and methods: In a retrospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(12 reference statements)
0
4
0
3
Order By: Relevance
“…In the Calisto trial, for example, almost 90% of patients with acute, symptomatic SVT suffered from varicose veins [11]. Our study revealed that the risk of SVT in primary CVD was associated with female gender and in both genders to the same extent, age-related [12].…”
mentioning
confidence: 52%
“…In the Calisto trial, for example, almost 90% of patients with acute, symptomatic SVT suffered from varicose veins [11]. Our study revealed that the risk of SVT in primary CVD was associated with female gender and in both genders to the same extent, age-related [12].…”
mentioning
confidence: 52%
“…Acute complications of CVI include thromboembolic events. In rare cases, superficial thrombophlebitis may develop, presenting as erythematous, tender, indurated, and warm cord or nodule . It can be associated with deep vein thrombosis (DVT) in about 18–25 % of patients and with pulmonary embolism in about 7 % .…”
Section: Complicationsmentioning
confidence: 99%
“…Als akute Komplikation der CVI sind thromboembolische Ereignisse zu nennen. In seltenen Fällen kann es zu einer oberflächlichen Venenthrombose (OVT) kommen, welche sich als geröteter, schmerzhafter, verhärteter und überwärmter Strang oder Knoten präsentiert und bei etwa 18–25 % der Patienten mit einer tiefen Beinvenenthrombose (TVT) und bei etwa 7 % mit einer Lungenembolie einhergehen kann . In Folge einer tiefen Beinvenenthrombose kann es bei 20–50 % der Patienten zu einem postthrombotischen Syndrom kommen (PTS) .…”
Section: Klinik Und Klassifikationunclassified